Valoración de enfermería en gestantes con ruptura prematura de membranas”.abril-agosto 2018 - Pillajo Guilcapi, Ariana Sofía (2018)
Nursing valuation is the first phase in the process performed by a nurse a patient, is it about the collection of data through the interview, observation and physical examination through domains according to author`s criteria, to identify factors and complications in pregnant women with Premature Membrane Rupture that is defined as a solution of continuity or loss of the integrity of the chorioamnmiotic membranes. Information was collected from 30 authors determining altered domains: 1. Health Promotion, 2. Nutrition, 3. Elimination, 4. Activity –Rest, 8. Sexuality, 11.Security/Protection, 12.Comfort, 13. Growth/Development; risk factors: infections in the urinary tract, anemia, multiple pregnancies, socioeconomic status, multiparty, smoking, maternal- gestational age, inadequate prenatal controls, presence of bacteria, polyhydramnios, sexually transmitted infections and leakocytosis; as well as complications such as cervical conization , intraanmiotic infection, neonatal death, low weight, neonatal- maternal infection, fever and maternal – fetal tachycardia, chorioamnionitis, and preterm birth.